(untitled) (Revista do Centro de Estudos Portugueses, 2002)
Este ensaio discute aspectos de recepção da obra de Alphonsus de Guimaraens no século XX. Coloca em evidência o diálogo entre o poeta simbolista e Mário de Andrade (1919), relatado no poema “A Visita”, de Carlos Drummond de Andrade. This essay discusses reception aspects of the Alphonsus de Guimaraens’ work in the 20th century. It places in evidence the dialogue among the simbolist poet and Mário de Andrade (1919), related in the poem A Visita (“The Visit”) by Carlos Drummond de Andrade.